Relationship of Fear of COVID-19 With Sexual Function and Sexual Satisfaction in Iranian Midwives: A Cross-sectional Study - Maryam Khodabakhshi; Homa Sadeghi Avval Shahr; Leila Amini; Shima Haghani (Iran University of Medical Sciences, 2023)
Background & Aims One of the consequences of the COVID-19 pandemic was its impact on marital relations. In health workers, including midwives, who have longer and more contact with mothers who may be infected with COVID-19, the fear of transmitting the virus to their partners is more. This fear can affect their personal lives, including sexual relationships and sexual health. This study aims to determine the relationship of the fear of COVID-19 with sexual function and sexual satisfaction in midwives working in teaching hospitals in Tehran, Iran. Materials & Methods This cross-sectional study was conducted on 122 midwives working in teaching affiliated to Iran University of Medical Sciences. They were selected using a census method from May 13 to August 6, 2022. Data collection tools included a demographic/ COVID-19-related form, Ahurso's fear of COVID-19 scale, female sexual function index (FSFI) and sexual satisfaction index. Data were analyzed in SPSS software, version 24.  Results The mean age of participants was 32.21‌±‌6.27 years. Most of them had a bachelor's degree. Sexual satisfaction had no significant relationship with any demographic factors (P>0.05). There was a negative and significant correlation (weak) between fear of COVID-19 and sexual satisfaction (r=-0.214, P=0.019). Also, there was a negative and significant correlation (moderate) between the fear of COVID-19 and sexual function (r=-0.450, P<0.001). Conclusion It seems that the fear of COVID-19 is related to sexual function and sexual satisfaction of Iranian married midwives. Therefore, during similar pandemics in the future, midwives need support such as receiving more personal protective equipment and stress management and resilience training workshops .